The Problem of the Foundations of Ethics in Postmodern Culture - Micevičiūtė, Jūratė (Problemos, 2002)
The article deals with the problem of the foundations of ethics in the postmodern culture. This culture is said to reject metanarratives as viable foundations for ethics, to be disappointed with the potential of history to provide some criterion for ethical judgement, and to allow the object to dominate, foreclosing any ethical statements about reality. (However, the author herself is not examining a broad question of the limits of the concept of postmodernity.) However, the social, scientific and ecological challenges of the second part of 2oth century have forced to resume the ethical discussion. After rejecting traditional rationalistic foundations of ethics by legal and natural Jaw, the principle of utility remained. The authors who resumed the discussion on ethics invoked the utilitarian philosophy. At the same time, they tried to overcome its limitations, first of all, the self-centredness of its criterion, which intensifies the lurid solipsism of society. One of the projects of this kind was the discourse ethics of J. Habermas, which made use of the achievements of thought of the last century including the respect for dignity and freedom of a person. He also made use of the philosophy of dialogue, which is grounded not in the individualistic anthropology, but in the anthropology of solidarity. Spanish-speaking female author A. Cortina has supplemented this theory by the analysis of the conditions of its application in the legal practice and everyday life. She made a distinction between “minimal ethics” and “maximal ethics”. The former has to harmonize different “maximal ethics” in the society and to ground the laws. Despite its limitations, the discourse ethics provides the space for continuation of the ethical discourse in the postmodern culture.
Keywords: grounding of ethics; discourse ethics; J. Habermas; A. Cortina